Mussel primed grafted zwitterionic phosphorylcholine based superhydrophilic/underwater superoleophobic antifouling membranes for oil-water separation - Kumar, A.; Nayak, K.; Münch, A. S.; Uhlmann, P.; Fery, Andreas; Tripathi, B. P. (Separation and Purification Technology, 2022)
One of the most successful methods for reducing membrane fouling in filtration and separation applications is zwitterionic surface modification. Herein, poly[(2-methacryloyloxyethyl phosphorylcholine)-co-(glycidyl methacrylate)] (poly(MPC-co-GMA)) was synthesized as a zwitterionic polymer and grafted onto the polysulfone (PSF) microfilter membrane using polydopamine chemistry. The stepwise modifications and formation of the zwitterionic PgEDgMG membrane were established by analyzing chemical structure, surface morphology, charge, and wetting properties. The antifouling properties were established by bovine serum albumin (BSA) protein adsorption as low as 3.71 ± 0.78 µg cm−2, fluorescence imaging, and in-situ BSA adsorption via zeta potential measurements. After zwitterionization, the in-air and underwater oil wetting tests demonstrate the formation of superhydrophilic and superoleophobic membranes, which are critical for oil-water separation. Finally, the prepared membranes were evaluated in batch and continuous mode for soybean and silicone oil-water emulsion separation. The modified membrane demonstrated nearly complete oil rejection (>99%) and flux recovery up to 99% after a continuous 10-cycle operation along with retention of initial flux during continuous filtration for 12 h. Overall, the combination of polydopamine and poly(MPC-co-GMA) created a robust zwitterionic antifouling surface which induces superhydrophilic character and can be used for long-term water purification and sep-aration applications.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Antifouling membrane; Oil-water separation; Water purification; Zwitterionic polymer